Representasi Betara Kala dalam Pertunjukan Teater Kontemporer Kalamanungsa - INDRA SUHERJANTO (Institut Seni Indonesia Yogyakarta, 2008)
Representation of Batara Kala in Contemporar Theater of Kalamanungsa. This Kalamanungsa theater tellshumanitarian issues, the journey of human life, human beings who have characters that need to fi nd a way out forthe better life. Starting from the myth Betara Kala that was born not intentionally emerges a wide range of results.Kalamanungsa will show something different. Existence Betara Kala, Kala Betara existence presented, and the mythof the birth of stalling and Betara Kala is an inspiring creation performance theater Kalamanungsa. Kalamanungsaraised the issue of modern society life with invented characters, with burdened by the dialogues that contain philosophy,poetry, with strong musical aspect. Kalamanungsa is showed with a modern theatrical approach, by presentingthe symbols to express meaning and emotion, using multimedia, projector/LCD, with music that is processed ona computer elaborated with a variety of traditional and modern musical instruments as the stage spectacle which isintentionally presented to give specifi c meaning. Theater performance Kalamanungsa tries to explain all elements ofart in a show, like music art, dance art, lighting and other art media with hope that Kalamanungsa will attend as ashow of modern theater.